Interleukin 9 single nucleotide polymorphisms rs17317275 association with celiac disease in Iraqi Population - Abbas, Ali Hafedh; Khudhair, Nagam; Ali, Shaimaa (Iraqi Journal of Science, 2025)
Celiac disease is a condition in which the small intestine’s lining is damaged and the body has trouble absorbing nutrients, typically occurring in individuals who are genetically susceptible and triggered by the consumption of gluten. The pathogenesis of this disease involves the interactions between environmental, genetics, and immunological factors. This research designed to inspect the frequencies of genotypes and alleles of IL-9 rs17317275 in an Iraqi celiac disease population via allele specific primers-polymerase chain reaction technology. The study included fifty patients with celiac disease, with a mean age of 23.5±11.88 years, preforming between November 2021 to February 2022. The results indicated that the AA genotype and A allele were significantly more frequent in celiac disease patients compared to the control group (72.0% vs. 10.9% OR:20.96, p= 1.98 x 10-16 and 84.0% vs. 34.0%, OR: 10.25, p= 2.4 x 10-8, respectively). Additionally, within the celiac disease group, the AA genotyping and A allele were more frequent in celiac disease group than the other genotypes and allele in the same group (72.0% and 84.0% vs. 24.0%, 4.0% and 16.0%, respectively). It can be concluded from the results that the AA genotype and the A allele may be related with a greater risk of developing digestive disorders than other genotypes.